Variation in tissue element concentrations in Quercus ilex L. over a range of different soils - CANADELL, J.; Vilà, M. (Plant Ecology, 1992)
In order to study the variability in nutrient concentrations in four tissues of Q. ilex in relation to soil properties, we selected fifteen stands in both Q uercus ilex forests and Q. ilex-Pinus halepensis mixed forests. These stands had developed on soils derived from eight different parent materials. Three soil groups were differentiated according to their chemical properties: calcareous soils, siliceous soils, and volcanic soils. Across sites, nutrient concentrations were generally less variable in current-year tissues than in older tissues. Nitrogen and potassium showed the lowest variability among sites, their concen- trations in current-year leaves ranging from 1.17°o to 1.39°i, for N and from 0.530{, to 0.68°o for K. There were few statistically significant correlations between tissue element concentrations, the most frequent being the antagonistic relationship between calcium and magnesium. Nitrogen concentration in current-year leaves was negatively correlated with soil chemical fertility (nitrogen, phosphorus and potassium). This may reflect a nutritional imbalance between nitrogen and other nutrients, some of which may be more limiting than nitrogen to Q. ilex growth in Catalonia forests. Negative correlations were also found between plant magnesium and soil calcium, and positive correlations between plant calcium and soil calcium.}
Keywords: N/P ratio; Nutrient antagonism; Plant nutrient concentrations; Plant-soil relationships; Soil fertility